PENGEMBANGAN POTENSI DAERAH BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) GUNA MENINGKATKAN PENDAPATAN DAERAH DAN MASYARAKAT - Sulfiana, Sulfiana; Rosmiati, Rosmiati; Muchtar, Asikin; Syukur, Anshar; Herawaty, Herawaty; Mariana , Lina (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
The purpose of this research is to improve community knowledge, especially sub-district officials, regarding the importance of ICT in developing regional potential and increasing community income. The tool used to determine the extent of employee and community understanding of ICT in the context of developing regional potential and regional income is to use a questionnaire. Questionnaires were distributed to sub-district officials and the community present, distributed via barcode containing several questions about Information and Communication Technology and regional potential. The results show that sub-district officials and the community still do not know how to use ICT, apart from that, the Padoang-Doangan community also does not have a sub-district website. With the role of ICT and village websites, they should be the main capital for the community in introducing the potential of their region so that it is better known globally.